Arts Evaluation and Assessment Measuring Impact in Schools and Communities (Springer International Publishing, 2018)
This book addresses the challenges faced by arts organizations, schools, and community-based settings when designing program evaluations and measuring artistic engagement and experience. With contributions from leaders in the field, this volume is an exemplary collection of complete program evaluations that assess music, theater, dance, multimedia, and the visual arts in a variety of contexts. .